Synthesis and characterization of mixed Amides-Imines and Amides-Azo Compound derived from Chrysanthemic acid and trimethoprim and study their biological activities - Mohammad F. Mesher; Barram A. Hama; Balqes A. Ahmed (مجلة جامعة الانبار للعلوم الصرفة, 2017)
Chrysanthemic acid, Trimethoprim, amides, Imines and azo compound : all found to have enormous biological activities in different directions such as medical , pharmaceutical pesticidal …etc. Accordingly combination of these functional in on compound expected to enhances their activities. Therefore mixed amides – imines and amides – diazo derived from trimethoprim and chrysanthemic acid, have been prepared by reaction of equimolar amount of these compound to form the corresponding mono amides , which on treatment of the remaining amino group of the trimethoprim with some aromatic aldehydes give the corresponding imines ; or diazo compounds on reaction with nitrous acid followed by reaction with aromatic phenols and naphthols . The structures of these derivatives were confirmed by their physical properties and spectroscopic techniques such as FT-IR ; 1Hnmr and mass spectrometry for selected compound. In addition the biological evaluation of the synthesized compound have been studied through the investigation of its capacity to scavenge the free radical (DPPH.) to give an inhibition at 50% concentration (IC50) , using the butylated hydroxyl toluene (BHT) as a control. This study reveals the highest scavenging for the azo derivatives .